.. q T 0 = (q/p)a (q/p)a − (q/p)T−10 if p ≠ q and qT0 = 1 − T0/a if p = q = 1/2.

Step-by-step explanation:

Suppose that there are two different solutions, p and q, in [a, b]. Thus p =g(p) q =g(q) p ≠ q The function g(x) satisfies the hypotheses of the mean-value … that g(p) –g(q) = (p – q) g׳(t) Because g(p) =p and g(q) = q, the left side of Eq. (1-3) may…

## Answers ( )

Answer:.. q T 0 = (q/p)a (q/p)a − (q/p)T−10 if p ≠ q and qT0 = 1 − T0/a if p = q = 1/2.

Step-by-step explanation:Suppose that there are two different solutions, p and q, in [a, b]. Thus p =g(p) q =g(q) p ≠ q The function g(x) satisfies the hypotheses of the mean-value … that g(p) –g(q) = (p – q) g׳(t) Because g(p) =p and g(q) = q, the left side of Eq. (1-3) may…